2019
DOI: 10.1021/acssuschemeng.8b04947
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-Friendly, Nanocellulose/RGO/in Situ Formed Polyaniline for Flexible and Free-Standing Supercapacitors

Abstract: There have been extensive demands for eco-friendly, lightweight, flexible, and high performance supercapacitors for advanced applications like wearable electronics, hybrid electric vehicles, and industrial grid storage. In this work, a metalless nanocellulose-based PANI/RGO electrode with excellent flexibility, mechanical strength, and conductivity was developed and assembled into sandwich-like supercapacitors. Reduced graphene oxide (RGO) was mixed into aniline during the in situ polymerization of PANI to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 64 publications
(119 reference statements)
1
45
0
Order By: Relevance
“…[ 229 ] Of particular interests are investigations on the fabrication of flexible and free‐standing PANI–graphene/cellulose electrodes and devices with high capacitance. [ 232,233,236 ] All‐solid [ 226 ] and flexible devices were fabricated and tested. The use of carbon fiber‐bridged PANI and graphene paper and bacterial cellulose allowed for the fabrication of a highly foldable all‐solid‐state supercapacitor.…”
Section: Conductive Polymer and Composite Electrodesmentioning
confidence: 99%
“…[ 229 ] Of particular interests are investigations on the fabrication of flexible and free‐standing PANI–graphene/cellulose electrodes and devices with high capacitance. [ 232,233,236 ] All‐solid [ 226 ] and flexible devices were fabricated and tested. The use of carbon fiber‐bridged PANI and graphene paper and bacterial cellulose allowed for the fabrication of a highly foldable all‐solid‐state supercapacitor.…”
Section: Conductive Polymer and Composite Electrodesmentioning
confidence: 99%
“…Conductive polymer polyaniline (PANI) is considered as a dependable pseudocapacitance material due to its fascinating properties such as its high specific capacitance, conductivity, environmental stability, and low cost . Usually, PANI can be synthesized by electrochemical synthesis, spin‐coating methods, and chemical oxidation and be widely applied . Yang et al fabricated PANI materials with nanocapsule structure, and the results showed high specific capacitance (502 F g −1 ) and outstanding cycle stability.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Usually, PANI can be synthesized by electrochemical synthesis, spin-coating methods, and chemical oxidation and be widely applied. [12][13][14] Yang et al 15 fabricated PANI materials with nanocapsule structure, and the results showed high specific capacitance (502 F g −1 ) and outstanding cycle stability. Qin's group 16 synthesized polyaniline via the interfacial polymerization, and the results showed that the isopropanol content affected the morphology of PANI chains and the specific capacitance of polyaniline.…”
Section: Introductionmentioning
confidence: 99%
“…FSCs have commanded a lot of concentration as one of the most important energy storage research focuses owing to their extraordinary capacitive behaviour, higher power density, higher rate capability, and higher cyclic stability in comparison with batteries and higher E d compared to the traditional capacitors [476], which provide them with a vast range of potential to be utilized in various applications. Each category of SC has its own specific features and applications, such as in portable/wearable electronic devices as well as in computer and mobile phones [2,477], high power sources for heavy lift trucks or cranes [478,479], the self-powered SCs in medical applications (e.g., flexible artificial skin, artificial intelligence, portable or implantable medical/biomedical devices) [480,481], solar applications [482][483][484]. There are several SC companies such as ELTON (Russia), Nesscap (Korea), CAP-XX (Australia), and Nippon Chemicon (Japan), which are developing various kind of SCs for different applications [485].…”
Section: Applications and Future Perspectivesmentioning
confidence: 99%